Encouraging bus use on a college campus: perception and usage of fixed route service - Wilson, Melissa A. (Kansas State University, 2017)
At Kansas State University, there is not an issue of opposition to public bus services. Instead, there is a perception that taking the bus is too complicated to figure out or cannot appropriately serve the community’s needs. This, combined with dependence and attachment to the automobile, caused local buses to become unpopular mode choices. Since the service is still relatively new, it has not been engrained into campus culture and ridership is very low. This study looked at the local bus system, ATA bus, used to access the Manhattan, KS campus of Kansas State University (KSU). According to the ATA Annual Report from 2014, 75% of off-campus students at KSU and 35% of employees live within five minutes of ATA city-wide routes (FHATA 2014). Ideally, all those students and employees would take the bus to class or work, but in reality, most walk or drive. A very small minority of students use the fixed route service, and many are unfamiliar with how the system works. A campus access survey distributed in March 2017 to the KSU community aimed to ascertain familiarity with the system, current level of use, as well as attitudes towards the existing public transportation system. The data recovered from the survey contradicts the hypothesis that the disuse of the bus system was due to an active opposition to public buses. Conversely, it pointed to the conclusion that disuse resulted from a lack of information about the bus service and a deep-set attachment to private automobiles. This research aimed to increase ridership by identifying attitudes towards transit among the KSU community and suggesting strategies for improving service.
Keywords: Public bus; Campus access; Ridership; Survey